Pengaruh financial literacy, financial knowledge, financial strain, financial attitude, dan debt terhadap financial satisfaction: financial behavior sebagai variabel mediasi - Dian Ulya Putra; Nadia Asandimitra (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2023)
The results of the Populix Survey show that the most common cause for someone experiencing mental disorders is financial problems. Financial satisfaction is one way to achieve the well–being of life that everyone wants. This quantitative research was conducted to examine the effect of financial literacy, financial knowledge, financial pressure, financial attitudes on financial satisfaction with financial behavior as a mediating variable in Kab. Sidoarjo The number of samples used is 225 respondents. The software used is AMOS version 24 with Structural Equation Modeling analysis technique. The collected data were analyzed using data analysis techniques in the form of validity test, reliability test, outlier test, normality test, suitability test, hypothesis test, coefficient of determination test (R2), and Sobel test. The results of this study indicate that financial literacy and financial strain have no effect on financial satisfaction. Meanwhile, financial knowledge, financial attitude, and debt have a significant effect on financial satisfaction. And financial behavior is able to mediate financial literacy and financial attitudes towards financial satisfaction.